De l'écran au tableau, I - Éric Brunier (Images Re-Vues)
Le Mystère Picasso, the movie that Clouzot directed with the painter, displays this modern art that has Picasso as a name and logic. So, the canvas as a translucent screen enact the show of a transformation without body, the place of shapes spontaneous generation' over the white screen movie. However, it would be without counting on the soundtrack and the movie in the movie, who dismantle the illusionistic machine.